Assurance of the existence of a trans‐boundary population of the snow leopard (Panthera uncia) at Tsagaanshuvuut – Tsagan‐Shibetu SPA at the Mongolia–Russia border - POYARKOV, Andrey D.; MUNKHTSOG, Bariushaa; KORABLEV, Miroslav P.; KUKSIN, Alexander N.; ALEXANDROV, Dmitry Y.; CHISTOPOLOVA, Maria D.; HERNANDEZ‐BLANCO, Jose Antonio; MUNKHTOGTOKH, Ochirjav; KARNAUKHOV, Alexander S.; LKHAMSUREN, Namdag; BAYARAA, Munkhtsog; JACKSON, Rodney M.; et al. (Integrative zoology, 2020)
The existence of a trans‐boundary population of the snow leopard (Panthera uncia) that inhabits the massifs of Tsagaanshuvuut (Mongolia) – Tsagan‐Shibetu (Russia) was determined through non‐invasive genetic analysis of scat samples and by studying the structure of territory use by a collared female individual. The genetic analysis included species identification of samples through sequencing of a fragment of the cytochrome b gene and individual identification using a panel of 8 microsatellites. The home range of a female snow leopard marked with a satellite Global Positioning System (GPS) collar was represented by the minimum convex polygon method (MCP) 100, the MCP 95 method and the fixed kernel 95 method. The results revealed insignificant genetic differentiation between snow leopards that inhabit both massifs (minimal fixation index [FST]), and the data testify to the unity of the cross‐border group. Moreover, 5 common individuals were identified from Mongolian and Russian territories. This finding clearly shows that their home range includes territories of both countries. In addition, regular movement of a collared snow leopard in Mongolia and Russia confirmed the existence of a cross‐border snow leopard group. These data support that trans‐boundary conservation is important for snow leopards in both countries. We conclude that it is crucial for Russia to study the northern range of snow leopards in Asia.